The effect of ultrafiltration transmembrane permeation on the flow field in a surrogate system of an artificial kidney - Matilde De Pascale; Monica Faria; Cristiana Boi; Viriato Semiao; Maria Norberta de Pinho; Mihriban O. Pekguleryuz (Experimental Results, 2021)
Renal Replacement Therapies generally associated to the Artificial Kidney (AK) are membrane-based treatments that assure the separation functions of the failing kidney in extracorporeal blood circulation. Their progress from conventional hemodialysis towards high-flux hemodialysis (HFHD) through the introduction of ultrafiltration membranes characterized by high convective permeation fluxes intensified the need of elucidating the effect of the membrane fluid removal rates on the increase of the potentially blood-traumatizing shear stresses developed adjacently to the membrane. The AK surrogate consisting of two-compartments separated by an ultrafiltration membrane is set to have water circulation in the upper chamber mimicking the blood flow rates and the membrane fluid removal rates typical of HFHD. Pressure drop mirrors the shear stresses quantification and the modification of the velocities profiles. The increase on pressure drop when comparing flows in slits with a permeable membrane and an impermeable wall is ca. 512% and 576% for $ CA22/5%SiO_2 $ and $ CA30/5%SiO_2 $ membranes, respectively.